Nasal rhinosporidiosis masquerading as pyogenic granuloma in a pediatric patient at a Zonal Referral Hospital in Central Tanzania: Case report - Zephania Saitabau Abraham; Francis Zerd; Aveline Aloyce Kahinga (Clinical Case Reports, 2022)
Abstract Being rare, rhinosporidiosis is a chronic granulomatous disease that is characterized by polypoidal lesions of the mucous membrane and is caused by Rhinosporidium seeberi. The disease commonly affects the mucous membrane of the nasopharynx, conjunctiva, and palate and its very rare in our geographical location.